The Spice Melange as a Catalyst to the Discovery of the Mind (Papers in Arts and Humanities, 2025)
Melange, or spice as it is also known, is an ingredient in Frank Herbert's novel Dune. It symbolizes the infinite possibilities of the human mind, as it is a source of knowledge and power. Both addictive and mind-altering, for the people of Arrakis, its source place, the spice is the basis of their lives and the cornerstone of their daily rituals. Due to its effect, the traditional lifespan is extended three times, but at the same time, its consumption causes a strong addiction. It is the basis of the rites of passage. The spice is a consciousness-expanding narcotic produced during the natural life cycle of sandworms, which has been the core of technological development and commerce since its discovery. Moreover, the formation of the cultural memory of the Fremen is made possible by the Water of Life, a substance transformed from poison and heavily saturated with spice. In tribal society, constant contact with the spice also manifests in physical changes, as the natural layer of their eyes turns otherworldly blue due to consumption. In my study, I address the following questions: can spice as a drug fully enhance the capabilities of the human mind? What is its role in the rites, and how does it enable the cultural memory of the tribe? What do various interest groups in the galaxy use it for? The core of my topic is the relationship between the spice and the individual through different social strata, ritual ceremonies, and the question of foresight.
Keywords: spice; people; sublime; navigators; cultural memory